Mario and the hole in the sky : how a chemist saved our planet - Rusch, Elizabeth; d (Watertown, MA : Charlesbridge, 2019)
A picture book that describes how Mexican American chemist Mario J. Molina discovered that CFCs, a chemical used in spray cans, was destroying Earth's protective ozone layer.
Kirkus Starred, September 2019
Includes bibliographical references.
3.7
K-3
Keywords: Molina, Mario J. -- Juvenile literature; Chemists -- Biography -- Juvenile literature; Nobel Prize winners -- Biography -- Juvenile literature; Ozone layer depletion -- Juvenile literature; Atmospheric ozone -- Juvenile literature; Air -- Pollution -- Juvenile literature; Molina, Mario J; Chemists; Nobel Prize winners; Mexican Americans -- Biography; Ozone layer depletion; Atmospheric ozone; Air -- Pollution; Creative nonfiction; Nonfiction picture books; Biographies